The transcriptional regulation of the human angiotensinogen gene after high-fat diet is haplotype-dependent: Novel insights into the gene-regulatory networks and implications for human hypertension - Rana, Anita; Jain, Sudhir; Puri, Nitin; Kaw, Meenakshi; Sirianni, Natalie; Eren, Deniz; Mopidevi, Brahma Raju; Kumar, Ashok (PloS one, 2017)
Single nucleotide polymorphisms (SNPs) in the human angiotensinogen (hAGT) gene may modulate its transcription and affect the regulation of blood pressure via activation of the renin-angiotensin aldosterone system (RAAS). In this regard, we have identified polymorphisms in the 2.5 Kb promoter of the hAGT gene that form two haplotype (Hap) blocks: -6A/G (-1670A/G, -1562C/T, -1561T/C) and -217A/G (-532T/C, -793A/G, -1074T/C & -1178G/A). hAGT gene with Hap -6A/-217A (Hap I) is associated with increased blood pressure whereas, Hap -6G/-217G (Hap II) is associated with normal blood pressure in human subjects. Since RAAS over activity contributes to hypertension in obesity, we have made transgenic mice (TG) containing either Hap I or Hap II of the hAGT gene to understand the role of obesity on its transcriptional regulation. Although, a high-fat diet (60% Kcal from fat, 12 weeks) elevates hAGT and mAGT regardless of haplotype, this effect is significantly (p<0.05) accentuated in Hap I mice, in both adipose and liver tissues. Chromatin Immuno- precipitation (ChIP) assay shows an increased binding of transcription factors including, GR, CEBPβ and STAT3 to the chromatin of the Hap I TG mice after high-fat diet as compared to Hap II TG mice (p<0.05). Differential plasma levels of hAGT in Hap II and I mice, after high-fat diet, further corroborate the variable transcriptional regulation of the hAGT, governed by gene-haplotypes. Taken together, our results show that SNPs in the Hap-I of the hAGT gene promote high-fat diet-induced binding of transcription factors GR, CEBP-β and STAT3, which lead to elevated expression of the hAGT gene in hepatic and adipose tissues.